The benefits of the dairy value chain to inclusive sustainable development in European highlands: a systems thinking approach - Ceppatelli, Andrea (2024)
This research investigates the benefits of the dairy value chain beyond food provision, and its contribution to inclusive sustainable development (ISDH) in European highlands. Transdisciplinary teams interviewed and analysed 11 cases related to the dairy value chain sourced from three highland regions in Europe: Alps (Austria, France, Italy), Massif Central (France), Pyrenees (Spain). Actors interviewed were farmers, cooperatives, retailers and associations. A systems thinking approach was applied to develop a conceptual map (Causal Loop Diagram, CLD) describing the contribution of the dairy value chain to ISDH, through the interpretation of the viewpoints of interviewed actors. For each case, the factors contributing to ISDH were identified, then clustered within related topics. Topics from all the cases were used to develop a CLD, and subsystems and leverage points identified. Six interconnected subsystems were identified: local resources, environment, dairy production, collaboration, supply chain and socioeconomic. Four leverage points were also identified: public subsidies, feed autonomy, certification of product, and added value. In conclusion, the dairy value chain provides the following benefits aligned with the dimensions of ISDH: landscape maintenance and ecosystem services, quality of dairy products and added value, inclusive governance for actors, reduction of environmental impact, and local development. This model delivers a decisionmaking tool for the actors involved in the dairy value chain, to prioritise strategic interventions.